Diagnosis of Functional Dyspepsia on the basis of Rome III clinical diagnostic criteria in a tertiary care hospital: A cross-sectional observational study - Biswas, Kaushik; Hazra, Rajdip; Chakraborty, Sisir; Bose, Rajarshi; Garain, Swadesh (Asian Journal of Medical Sciences, 2018)
Background: Though functional dyspepsia (FD) is often a diagnosis of exclusion, whether minor mucosal gut pathology represents organic disease or FD, it still remains controversial.Aims and Objectives: The present study has been conducted to determine the accuracy of symptom based diagnosis of FD based on Rome III diagnostic criteria in a tertiary care center.Materials and Methods: Total 140 patients aged between 18-55 years of both sexes with upper abdominal symptoms without known or post investigational organic diseases, were included in this study. Patients fulfilling the Rome III criteria were diagnosed as FD and undergone upper GI endoscopy (UGIE). Those devoid of organic lesions were confirmed as ‘true FD’.Results: Out of 140 study patients, 100 patients fulfilled Rome III criteria (clinical FD) out of which 77 were confirmed as ‘true FD’ after UGIE with an accuracy of 83.57 %.Conclusion: Rome III clinical criteria can be applied to diagnose FD in a tertiary care center with some limitations. The authors suggest some modification of Rome III criteria.Asian Journal of Medical Sciences Vol.9(1) 2018 55-60